A clinico-pathological and neuro-radiological study of angiomatous meningioma: Aggressive look with benign behaviour. (January 2021) - Verma, Pawan K.; Nangarwal, Bhawan; Verma, Jyoti; Dwivedi, Vikas; Mehrotra, Anant; Das, Kuntal Kanti; Maurya, Ved P.; Bhaisora, Kamlesh S.; Singh, Jaskaran; sardhara, Jayesh; Srivastava, Arun Kumar; Behari, Sanjay; et al.
Highlights: Angiomatous meningioma is a rare subtype of meningioma with paucity of literature. Clinical, radiological features and a surgical outcomes were investigated in the study. Angiomatous meningioma showed a distinctive radiological features and intraoperative consideration with nearly similar surgical outcome compared to meningioma in general. Pre-operative anticipation helps us to improve the patient safety and surgical outcome. Subtotal excision should be opted if chance of complication is high. Abstract: Angiomatous meningioma is a rare variant tumor classified as WHO grade 1 meningioma and accounts for about 2.1% of all meningioma. Their clinical presentation, surgical management, and prognosis are almost similar to the classical meningioma. Despite of benign nature and being comparatively small in size, they look aggressive on radiology images like massive peritumoral edema and intense contrast enhancement. Being a unique subtype of meningioma, the studies on angiomatous meningioma are very limited. In this cross sectional retrospective study, we described the clinical presentation, radiology, histopathological features and differential diagnosis of 30 cases of angiomatous meningioma from a single centre. The clinical parameters include demographic profile, symptoms and radiological findings including location, extent, pattern, histopathology with World Health Organization (WHO) grade-2016, extent of tumour excision, recurrence and surgical outcome. Incidence of angiomatous meningioma in our study was 2.46% with male predominance. The most common location in our study was convexity. 27 out of 30 had histopathology reports of angiomatous meningioma and 3 had lipoangiomatous meningioma. The high vascularity and disproportionate peri -tumoral edema makes it a surgical challenge for excision. The complications and surgical outcome were analysed. The radiological anticipation of tumour subtype, meticulous pre-operative planning and intraoperative precautions remains a key for success.